2007
DOI: 10.1007/s11104-007-9228-2
|View full text |Cite
|
Sign up to set email alerts
|

Root, shoot tissues of Brassica juncea and Cereal secale promote potato health

Abstract: Brassica species are increasingly being used as cover crops to suppress soil-borne diseases in potato cropping systems. Experiments were conducted in controlled environments and in the field to evaluate the effects of cover crop root or shoot or a combination of root and shoot tissues on potato root and tuber health. In a lab assay we examined the extent to which volatile compounds released from tissues of two cover crop species, rye (Cereale secale L.) and oriental mustard (Brassica juncea L.), could inhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 37 publications
3
18
0
Order By: Relevance
“…The consistent and significant inhibition of targeted organisms by certain cultivated grasses demonstrated in these experiments is not surprising, given many previous reports of lethal or inhibitory effects against various plant pests (see e.g. Miller 1996;Snapp et al 2007;Wardle et al 1996). A portion of the below-ground, inhibitory activity of grass family members results from production of toxic, decomposition compounds (see e.g.…”
Section: Discussionsupporting
confidence: 79%
“…The consistent and significant inhibition of targeted organisms by certain cultivated grasses demonstrated in these experiments is not surprising, given many previous reports of lethal or inhibitory effects against various plant pests (see e.g. Miller 1996;Snapp et al 2007;Wardle et al 1996). A portion of the below-ground, inhibitory activity of grass family members results from production of toxic, decomposition compounds (see e.g.…”
Section: Discussionsupporting
confidence: 79%
“…compare canola and rapeseed) and was observed for ryegrass indicating other non-GSL mechanisms were involved, especially for Rhizoctonia. Snapp et al (2007) demonstrated that incorporation of mustard (B. juncea) plants was effective in reducing soil-borne fungi, principally Rhizoctonia and promoting healthy roots and tubers. Compared to bare fallow, a rye cover crop increased the disease rating of tubers by 37% while an Indian mustard cover crop reduced it by 25% (Table 9.1).…”
Section: Brassica Green Manures In Potato Production Systems 9821mentioning
confidence: 99%
“…Upon tissue damage, glucosinolates are degraded by the enzyme myrosinase, thereby forming toxic breakdown products such as (iso)thiocyanates (Wang et al 2009). Belowground, glucosinolates and their breakdown products are known to reduce the abundance of phytophagous organisms such as rootfeeding nematodes (Lazzeri et al 2004;Potter et al 1998;Potter et al 2000), fungi (Bressan et al 2009;Rumberger and Marschner 2003;Snapp et al 2007), and bacteria (Aires et al 2009;Bressan et al 2009;Rumberger and Marschner 2003). Aromatic glucosinolates, particularly gluconasturtiin and its breakdown product 2-phenylethyl isothiocyanate, are generally considered as the most toxic glucosinolates in plant roots (Potter et al 1998;Potter et al 2000;Rumberger and Marschner 2003;van Dam et al 2009;Vierheilig et al 2000).…”
Section: Introductionmentioning
confidence: 99%